Peran Pengetahuan Gizi Ibu dan Pemberian ASI Ekslusif Dalam Pencegahan Stunting Pada Balita Usia 24-59 Bulan - Lilis Maghfuroh; Indy Pradita; Harnina Samantha Aisyah (Poltekkes Kemenkes Maluku, 2025)
Stunting occurs when toddler has length or height less than minus two standard deviations below the median child growth standard. This condition caused by chronic malnutrition that occurs since baby the womb and the early period after baby born which only appears when child is 2 years old. This study aims to determine relationship between maternal knowledge about nutrition and exclusive breastfeeding with incidence of stunting in toddlers aged 24-59 months. Research design used analytic correlation with a cross sectional approach. Population was 140 mothers and toddlers aged 24-59 months, using simple random sampling technique obtained as many 104 respondents. Research instrument used a questionnaire, stadiometer and height growth chart according to age. Based on results of study using Spearman Rank test, value of p=0,000 (<0,05) means that there is relationship between maternal knowledge and incidence of stunting in toddlers aged 24-59 months and results of Contingency Coefficient test obtained value of p=0,000 (<0,05) means that there is relationship between exclusive breastfeeding with incidence of stunting in toddlers aged 24-59 months. It is hoped that role of health workers such as midwives and nutritionists to provide education to mothers of toddlers about importance of exclusive breastfeeding and knowledge about nutrition.